An Australian geography of unhealthy housing. (13th February 2019) - Baker, Emma; Lester, Laurence; Beer, Andrew; Bentley, Rebecca
Abstract: Housing problems, such as affordability, poor quality of condition, or damp, are key determinants of health and wellbeing. Importantly, though, a growing body of research has shown that unhealthy housing is the combined result of multiple housing problems acting together. Although the spatial distribution of discrete housing problems is well established, little is known of Australia's geography of unhealthy housing. We have previously defined and validated an Australian Index of Housing Insults, which captures the multiple ways in which housing adversely influences individual health—including, but not limited to, people's tenure security, affordability, quality, and neighbourhood characteristics. Using the Household Income and Labour Dynamics in Australia (HILDA) dataset, a nationally representative longitudinal survey of Australian households, this paper describes Australia's geography of unhealthy housing. The analysis examines the prevalence, characteristics, and distribution of the population who are vulnerable to unhealthy housing. Our findings reveal both a worsening landscape of households at risk because of their accommodation and a changing pattern of unhealthy housing in Australia over time. The paper considers how these findings may impact future policy settings and the potential to improve the health of Australia's population through targeted housing interventions.